2020
DOI: 10.20944/preprints202010.0341.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 and Environmental Samples: A Methodological Approach to Have Consistent and Comparable Results

Abstract: Since the beginning of coronavirus disease 2019 (COVID-19) pandemic, large attention has been focused on the relationship between SARS-CoV-2 diffusion and environment. As a matter of fact, clear evidence of the transmission of SARS-CoV-2 via respiratory aerosol would be of primary importance; at the same time, checking the presence of SARS-CoV-2 in wastewater can be extremely useful to control the diffusion of the disease. Up to now, many studies report SARS-CoV-2 concentrations in indoor/outdoor air samples o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Several studies have suggested that SARS-CoV-2 can transmit through various indoor and outdoor aerosols, particularly by PM ( Robotto et al, 2021 ; Senatore et al, 2021 ). Natural and anthropogenic sources such as industrial activities, domestic heating, and road transport in urban areas could contribute to PM production ( Bontempi, 2020 ).…”
Section: Impact Of Pm In Covid-19 Infectionmentioning
confidence: 99%
“…Several studies have suggested that SARS-CoV-2 can transmit through various indoor and outdoor aerosols, particularly by PM ( Robotto et al, 2021 ; Senatore et al, 2021 ). Natural and anthropogenic sources such as industrial activities, domestic heating, and road transport in urban areas could contribute to PM production ( Bontempi, 2020 ).…”
Section: Impact Of Pm In Covid-19 Infectionmentioning
confidence: 99%